The Systemic Image : A New Theory of Interactive Real-Time Simulations - Hinterwaldner, Inge (Book collections on Project MUSE., 2017)
In media art history as well as in science studies an intensified reception of cybernetic and system-theoretical concepts can be seen in the last few years. In this work, a conceptualization of the relationship between the systemic and the iconic in interactive real-time simulations is proposed.